Coffee, Caffeine-Related Genes, and Parkinson's Disease: A Case–Control Study - Facheris, Maurizio F. (Mov Disord, 2008)
An inverse association between coffee and Parkinson's disease (PD) has been reported. However, it remains uncertain why some but not all coffee drinkers are less susceptible to PD. We considered the possibility of a pharmaco-genetic effect. In our study, we included 1,208 subjects (446 case-unaffected sibling pairs and 158 case-unrelated control pairs) recruited from an ongoing study of the molecular epidemiology of PD in the Upper Midwest (USA). We collected information on lifetime coffee drinking and we studied two genes: ADORA2A, which encodes the major receptor activity of caffeine in the brain (variants rs5751876 and rs3032740), and CYP1A2, which encodes the major rate-limiting step of caffeine metabolism (variants rs35694136 and rs762551). We did not observe significant associations of coffee drinking or of the genetic variants with PD susceptibility, either independently or jointly, in the sample overall and in most strata. Our study neither supports the hypothesis that coffee protects against PD nor provides evidence for a pharmacogenetic effect.